State of The Art Evolution of Adsorption Wastewater From Crude Palm Oil Industries - Meutia Mirnandaulia; Li Idi'il Fitri; Mustakim Mustakim; Muhammad Fadli Khairul (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Wastewater from crude palm oil production is among the most concentrated agro-industrial effluents, characterized by very high organic loads, suspended solids, and variable composition. Conventional treatments often struggle to consistently remove recalcitrant pollutants, such as phenolics, colored compounds, and emulsified oil. As a result, adsorption has gained global attention as a versatile and efficient alternative method. This review summarizes the recent advances in adsorption technologies for crude palm oil wastewater treatment. This review highlights the progress in adsorbent development, including biochar, mineral composites, layered double hydroxides, magnetic hybrids, and other engineered materials. The key removal mechanisms for organics, nutrients, and colloids are examined, alongside insights from kinetic, isotherm, and thermodynamic studies. The integration of adsorption with biological, membrane, and oxidation processes is also discussed, demonstrating improved removal efficiency and enhanced effluent stability compared to individual processes. Major challenges remain, particularly in terms of mechanical stability, regeneration, competitive adsorption, and large-scale validation. Future research should prioritize process intensification, sustainable regeneration methods, circular economy-based adsorbent production, and life cycle assessment. Overall, adsorption represents a promising pathway toward more sustainable and reliable crude palm oil wastewater management